itu OPTIMASI SEDIAAN NANOEMULGEL KOMBINASI TITANIUM DIOXIDE, ZINK OXIDE DAN NIACINAMIDE SEBAGAI SUN PROTECTION FACTOR PADA FORMULASI SUNSCREEN: Hasil Data Titanium Dioksida, Zink Oksida dan Niacinamide - Rahmadani, Widya (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2024)
Excessive exposure to ultraviolet (UV) radiation can lead to various skin disorders, including premature aging, hyperpigmentation, and skin cancer, making the use of sunscreen an essential step in skin protection. Titanium dioxide and zinc oxide are physical sunscreen agents that work by reflecting and absorbing UV rays, while niacinamide serves as an antioxidant, anti-inflammatory agent, and skin barrier enhancer. The combination of these three ingredients in a nanoemulgel formulation has the potential to enhance UV protection efficacy while improving formulation characteristics. The optimization of nanoemulgel focuses on improving physical stability, SPF efficacy, and user comfort, which are influenced by particle size, surfactant selection, and homogenization methods. Nano-sized particles (<200 nm) of titanium dioxide and zinc oxide allow for more uniform skin coverage and reduce the white cast effect, while the nanoemulgel delivery system increases the bioavailability of active ingredients and prolongs UV protection duration. Studies have shown that combining titanium dioxide, zinc oxide, and niacinamide in a nanoemulgel significantly increases SPF compared to conventional formulations while providing additional benefits such as anti-inflammatory effects and improved formulation stability. The appropriate selection of oil and surfactant components also determines the viscosity, physical stability, and spreadability of the formulation. Therefore, nanoemulgel-based formulations represent an innovative approach to developing sunscreens that are more effective, stable, and user-friendly. Further studies through in vivo and clinical testing are necessary to ensure long-term safety and efficacy.